The Efficiency of Zakah Institutions Using Data Envelopment Analysis - Rusydiana, Aam Slamet; Al Farisi, Salman (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
Although social based, but in its management the Zakah Institutions need to uphold professionalism, transparency and accountability. Most recently, in the measurement of the effectiveness of the management of zakah fund, known Zakah Core Principles concept. This study would try to measure the efficiency of 3 (three) Zakah Institutions with Data Envelopment Analysis (DEA) method. Banxia Frontier Analyst 3.1 used in data calculation. The calculation of the level of Zakah Institutions efficiency in this study are relative, not absolute. The results show that there is 12 fully efficient Decision Making Unit (DMU) Zakah Institution (100% efficient) and 6 DMU inefficient. The main factor inefficiency Zakah Institution from 2007 to 2014 due to the distribution of zakah funds to ashnaf. It is still less than optimal. So it has not been able to resolve the problem of poverty. DOI: 10.15408/aiq.v8i2.2876